An Exploratory Study on Corporate Governance Development in Brazilian Enterprises - Marinelli, Marcos (Review of Business Management, 2007)
This article presents the generation and systematization of knowledge, leading to conceptual, theoretical and applied reflexions about corporate governance as well as its contribution to organizational development. It is structured in four parts: the first one contains the introduction; the second is related to the theoretical support; the third refers to corporate This article presents the generation and systematization of knowledge, leading to conceptual, theoretical and applied reflections about corporate governance as well as its contribution to organizational development. It is structured in four parts: the first one contains the introduction; the second is related to the theoretical support; the third refers to corporate governance in Brazil and in the world. In the fourth part portrays secondary researches about the application of governance proving that there are positive influences in the results of the organizations which are object of the case studies. Key-words: Corporate governance. Council of administration. Best practices for corporative governance for Stakeholders